Apigenin inhibits STAT3/CD36 signaling axis and reduces visceral obesity. (February 2020) - Su, Tao; Huang, Chunhua; Yang, Chunfang; Jiang, Ting; Su, Junfang; Chen, Minting; Fatima, Sarwat; Gong, Ruihong; Hu, Xianjing; Bian, Zhaoxiang; Liu, Zhongqiu; Kwan, Hiu Yee
Graphical abstract: Abstract: Visceral obesity is the excess deposition of visceral fat within the abdominal cavity that surrounds vital organs. Visceral obesity is directly associated with metabolic syndrome, breast cancer and endometrial cancer. In visceral obese subjects, signal transducer and activator of the transcription 3 (STAT3) in adipocytes is constitutively active. In this study, we aimed to screen for dietary herbal compounds that possess anti-visceral obesity effect. Apigenin is abundant in fruits and vegetables. Our data show that apigenin significantly reduces body weight and visceral adipose tissue (VAT), but not subcutaneous (SAT) and epididymal adipose tissues (EAT), of the high fat diet (HFD)-induced obese mice. Mechanistic studies show that HFD increases STAT3 phosphorylation in VAT, but not in SAT and EAT. Further studies suggest that apigenin binds to non-phosphorylated STAT3, reduces STAT3 phosphorylation and transcriptional activity in VAT, and consequently reduces the expression of STAT3 target gene cluster of differentiation 36 (CD36). The reduced CD36 expression in adipocytes reduces the expression of peroxisome proliferator-activated receptor gamma (PPAR-γ) which is the critical nuclear factor in adipogenesis. Our data show that apigenin reduces CD36 and PPAR-γ expressions and inhibits adipocyte differentiation; overexpression of constitutive active STAT3 reverses the apigenin-inhibited adipogenesis. Taken together, our data suggest that apigenin inhibits adipogenesis via the STAT3/CD36 axis. Our study has delineated the mechanism of action underlying the anti-visceral obesity effect of apigenin, and provide scientific evidence to support the development of apigenin as anti-visceral obesity therapeutic agent.